Clinical characteristics, time course, and outcomes of major bleeding according to bleeding site in patients with venous thromboembolism. Issue 211 (March 2022) - Bikdeli, Behnood; Moustafa, Fares; Nieto, José Antonio; Lee, Alfred I.; Ruíz-Giménez, Nuria; Lorenzo, Alicia; Schellong, Sebastian; Soler, Silvia; Ortíz, Salvador; Morales, Mª. Del Valle; Bosevski, Marijan; Gavín, Olga; et al.
Abstract: Background: Bleeding is the most dreaded complication of anticoagulant therapy for acute venous thromboembolism (VTE). Limited data exist about patient characteristics, time course and outcomes of major bleeding, according to the bleeding site. Methods: We used the data from the Registro Informatizado Enfermedad TromboEmbólica (RIETE) registry (03/2001–07/2018) and identified patients who suffered from major bleeding during anticoagulation. We assessed patient characteristics, time course, and 30-day outcomes including mortality, re-bleeding, and VTE recurrences, according to bleeding site. Results: Among 78, 136 patients with VTE receiving anticoagulation, 2244 (2.9%) suffered from major bleeding (gastrointestinal in 800, intracranial in 417, hematoma in 410, genitourinary in 222, retroperitoneal in 145; other sites in 250). There were variations in baseline characteristics, including older age ( P < 0.001) and predominance of women (70.2% [95% confidence interval [CI]]: 65.6–74.6% versus 50.5%, 95% CI: 48.2–52.9, P < 0.001) in patients with hematoma, compared with other patients. Overall, 82.7% of hematomas and 81.4% of retroperitoneal bleeds occurred in the first 90 days after the diagnosis of the VTE event, compared with only 50.6% of intracranial bleeds. Across the bleeding subgroups, 30-day all-cause mortality rates were highest in patients who suffered from intracranial bleeding (41.0%; 99% confidence interval [CI]: 34.8–47.4%), and lowest in patients who suffered from hematoma (17.8%; 99% CI: 13.2–23.2%). Patients who suffered from a major bleeding event in the first 30 days after VTE had significantly higher odds at 90-day follow-up to develop mortality (including from bleeding), recurrent VTE, and recurrent major bleeding (all Ps < 0.001). Variations were observed in the results according to the bleeding site. Conclusions: Major bleeding is a serious complication in VTE patients. Patient characteristics, time course and outcomes varied substantially according to the bleeding site. Additional studies are needed to tease out the impact of patient risk factors, treatment regimens, and a potential distinct effect from the site of bleeding. Trial registration: https://clinicaltrials.gov/ct2/show/NCT02832245 (RIETE registry). Highlights: In a large of study of patients with major bleeding in the course of anticoagulation for venous thromboembolism (VTE), there were distinctions in the time course of bleeding events according to the bleeding site. Intracranial bleeds accrued gradually over the course of a year, whereas most of the hematomas and retroperitoneal bleeds occurred within the first 30 days. Patient characteristics had distinctions based on the site of bleeding, including older age and a greater proportion of women among patients who had hematoma. Among patients with major bleeding, 30-day mortality rates were highest in those who had intracranial hemorrhage.